2004
DOI: 10.1002/ijc.20283
|View full text |Cite
|
Sign up to set email alerts
|

Expression in bladder transitional cell carcinoma by real‐time quantitative reverse transcription polymerase chain reaction array of 65 genes at the tumor suppressor locus 9q34.1‐2: Identification of 5 candidates tumor suppressor genes

Abstract: Frequent deletions on 9q34.1-2 were reported in bladder transitional cell carcinoma. High deletion mapping studies delimited a critical interval between markers D9S61 and D9S66, which is highly susceptible to contain a tumor suppressor gene. Expression level of the 65 genes localized in this region was analyzed by real-time quantitative RT-PCR, comparing tumor to normal urothelium. Five genes exhibited a significantly reduced expression level: C9orf9, KIAA0625, ABL1, LAMC3 and KIAA1857-netrin-G2, which exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…4i). SPACA9 was reported to be a tumor suppressor (68, 69) that possess a poly-glutamine domain (4 residues) of unknown function. This protein has previously been shown to localize in the cytoplasm of the cells where it is associated with cytoplasmic microtubules (70).…”
Section: Resultsmentioning
confidence: 99%
“…4i). SPACA9 was reported to be a tumor suppressor (68, 69) that possess a poly-glutamine domain (4 residues) of unknown function. This protein has previously been shown to localize in the cytoplasm of the cells where it is associated with cytoplasmic microtubules (70).…”
Section: Resultsmentioning
confidence: 99%
“…In cancers that do not have the BCR–Abl translocation, ABL1 seems to show reduced expression. A study of bladder transitional cell carcinoma found a significant reduction in ABL1 expression in cancerous compared with normal tissue (Amira et al , 2004). In PCa progression, we found ABL1 to be downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…LAMC3 gene encodes laminins, which are the major non-collagenous constituent of basement membrane. LAMC3 mutations are associated with several cancers, including colon cancer, lung cancer, and melanoma, and candidate tumor suppressor genes in bladder transitional cell carcinoma [26]. LAMC3 is involved in the phosphatidylinositol 3-kinase.Akt signaling pathway, since it has a role in cell adhesion.…”
Section: Discussionmentioning
confidence: 99%